2002
DOI: 10.1042/cs1030101
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensinogen M235T gene polymorphism and recurrent restenosis after repeated percutaneous transluminal coronary angiography

Abstract: The present study was designed to prospectively test the hypothesis that gene polymorphisms of the renin-angiotensin system are associated with recurrent restenosis after repeated percutaneous transluminal coronary angioplasty. Five hundred and eleven patients after first successful angioplasty were characterized with respect to the angiotensinogen M235T, angiotensin-converting enzyme insertion/deletion and angiotensin II type 1 receptor A1166C gene polymorphisms. In 164 of these patients repeated angioplasty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Similarly, patients with the T allele of the angiotensinogen 235 M/T gene polymorphism have been shown to have elevated plasma angiotensinogen concentrations, which may also reflect an activated renin-angiotensin system. A number of studies have found associations between the angiotensinogen 235T allele and cardiovascular diseases including coronary artery disease [6] and restenosis [7] as well as recurrent restenosis [8] after initial and repeated percutaneous transluminal coronary angioplasty, respectively. The present study was designed to investigate whether the angiotensinogen 235 M/T genotype affects the mid-term outcome after coronary artery bypass graft surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, patients with the T allele of the angiotensinogen 235 M/T gene polymorphism have been shown to have elevated plasma angiotensinogen concentrations, which may also reflect an activated renin-angiotensin system. A number of studies have found associations between the angiotensinogen 235T allele and cardiovascular diseases including coronary artery disease [6] and restenosis [7] as well as recurrent restenosis [8] after initial and repeated percutaneous transluminal coronary angioplasty, respectively. The present study was designed to investigate whether the angiotensinogen 235 M/T genotype affects the mid-term outcome after coronary artery bypass graft surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The gene coding for the AT1R (AGTR1) contains a single nucleotide sequence variation (c.1166A4C) in the 3 0 -untranslated region, which has been reported to be associated with essential hypertension [Bonnardeaux et al, 1994]. While several studies [Völzke et al, 2000;Hertwig et al, 2002;Hamon et al, 1998;Okamura et al, 1999] failed to demonstrate an association between this sequence variation and restenosis after PTCA, one study [Völzke et al, 2005] reported that the sequence variation may modulate the effects of age on total mortality after CABG surgery.…”
Section: Gross Et Al [2004]mentioning
confidence: 96%
“…In the initial study [Völzke et al, 2000], carriers of the c.803C variant had an odds ratio for developing restenosis after PTCA of 1.43 (95% confidence interval 1.06-1.93) when compared to c.803TT homozygotes. The association of the c.803C variant with an increased risk of restenosis was corroborated in a follow-up study [Hertwig et al, 2002] involving all those patients from the previous study [Völzke et al, 2000] who had suffered from restenosis and were consecutively subjected to a second PTCA procedure. In the follow-up study [Hertwig et al, 2002] carriers of the c.803C variant had an odds ratio for developing recurrent restenosis after repeated PTCA of 2.56 (95% confidence interval 1.11-5.89) when compared to TT homozygotes.…”
Section: Gross Et Al [2004]mentioning
confidence: 97%
See 2 more Smart Citations